PENGARUH TEKNIK RELAKSASI TERHADAP PENURUNAN TINGKAT KECEMASAN PASIEN PRAOPERATIF - Sari, Febria Syafyu (Menara Ilmu, 2017)
Results of the study 56 countries in 2014 is estimated to number around 234 million surgical procedures per year, estimated complication rates following surgery (3-16%) and mortality (0,4-0,8%). The purpose of this study was to determine the effect of relaxation techniques to decrease the level of patient preoperative anxiety in surgical  wards Hospital Dr. Achmad Mochtar Bukittinggi. This research uses experimental research design to study design quasi experimental design. The study was conducted Bangsal Surgical Hospital Dr. Achmad Mochtar  Bukittinggi. Populasi in this study amounted to 68 people. The sampling technique is purposive sampling, with a sample of 12 people. Computerized data processing is done using SPSS(Statistical Package for the Social Sciences) with univariate and bivariate analysis, statistical test used was paired t-test. Hasil univariate analysis showed that 6 respondents did relaxation breath In, 3 respondents have mild anxiety level (50%). Statistical test results obtained p value = 0,001 so it can be concluded that there is a significant correlation between the influence of deep breathing relaxation techniques to decrease anxiety levels of patients praoperatif. It is expected that health care institutions to improve the program of relaxation techniques breath In. Keywords         :  Anxiety Level, Relaxation Technique